A Comparative Analysis of The Intrinsic Elements in Bumi Cinta and Ketika Cinta Bertasbih by Habiburrahman El Shirazy - Choeirul Azhar (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to compare the intrinsic elements of Bumi Cinta and Ketika Cinta Bertasbih by Habiburrahman El Shirazy using a structural literary approach. A qualitative descriptive method with comparative analysis was employed to examine the similarities and differences in theme, characterization, plot, setting, point of view, language style, and moral message. The data consisted of textual excerpts selected from both novels and analyzed based on the structural theory of fiction proposed by Nurgiyantoro. The findings indicate that both novels consistently promote Islamic values through themes of faith, love, and moral integrity while employing similar narrative perspectives and religious language styles. However, they differ in narrative setting, plot structure, character development, and conflict. Bumi Cinta portrays the struggle to maintain faith within a secular environment, whereas Ketika Cinta Bertasbih emphasizes responsibility, perseverance, and spiritual maturity in a religious setting. These findings demonstrate Habiburrahman El Shirazy's ability to express consistent ideological values through diverse narrative structures, thereby contributing to comparative literary studies and the appreciation of contemporary Indonesian Islamic fiction.